2022
DOI: 10.1109/lra.2022.3153989
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Anomaly Detection for Robot Navigation With Multi-Sensor Fusion

Abstract: Despite the rapid advancement of navigation algorithms, mobile robots often produce anomalous behaviors that can lead to navigation failures. The ability to detect such anomalous behaviors is a key component in modern robots to achieve high-levels of autonomy. Reactive anomaly detection methods identify anomalous task executions based on the current robot state and thus lack the ability to alert the robot before an actual failure occurs. Such an alert delay is undesirable due to the potential damage to both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…N. Dwek et al [ 26 ] designed sensor fusion and outlier detection to improve robust Ultra Wide Band positioning performance. T. Ji et al [ 27 ] used fault detection for navigation failure in agricultural environments to combat sensor occlusion in cluttered environments.…”
Section: Related Workmentioning
confidence: 99%
“…N. Dwek et al [ 26 ] designed sensor fusion and outlier detection to improve robust Ultra Wide Band positioning performance. T. Ji et al [ 27 ] used fault detection for navigation failure in agricultural environments to combat sensor occlusion in cluttered environments.…”
Section: Related Workmentioning
confidence: 99%
“…The recent adoption of a SVAE model for identifying critical underlying factors for prediction demonstrates the promising potential for application in robotic grasping. [33] This study investigates the transferability of grasping knowledge from on-land to underwater via a vision-based soft robotic finger that learns 6D forces and torques (FT) using SVAE. Using real-time images collected from an in-finger camera that captures the soft finger's whole-body deformations while interacting with physical objects on-land and underwater, we established a learning-based approach to introduce tactile intelligence for soft, delicate, and reactive grasping underwater, making it a promising solution to support scientific discoveries in interdisciplinary research.…”
Section: Machine Learning For Latent Intelligence In Tactile Roboticsmentioning
confidence: 99%
“…The recent adoption of a SVAE model for identifying critical underlying factors for prediction demonstrates the promising potential for application in robotic grasping. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although recent research efforts have made noteworthy progress on developing trustworthy robot autonomy [16,34,40], the deployment of low-cost robots in real-world environments has shown that they usually face difficulties in completing the tasks independently [32]. For example, due to the environmental complexity and terrain variability in agricultural environments, compact field robots (Figure 1a) deployed between rows of crops may fail the navigation task and get stuck in error states (Figure 1b), in which physical assistance from a human supervisor is required to continue the robot task [14,15]. To ensure the smooth operation of such multi-robot systems, the supervision and management of robot fleets are necessary in the presence of imperfect autonomy.…”
Section: Introductionmentioning
confidence: 99%